How COVID-19 has Been Transforming the Notion of Care - María Victoria López López (Universidad de Antioquia, 2020)
The year 2020 surprised us with COVID-19, which expanded throughout Asia and Europe and became a pandemic, reaching Latin America and our cities and everything seemed to change, including the most intimate and private relationships of social life in general, with repercussions in the human condition that lead to thinking about its setbacks. For the population not expert in epidemiology, it results quite difficult to understand what is happening and know what to do and how to assimilate discourses that break into the private sphere and - at the same time - amalgamate with social, environmental, economic, political, and other problems that even lead epidemiologists themselves to new reflections they thought already overcome. But also, within this context positive issues are unveiled, like solidarity, reflecting on consumerism, and caring for nature.